GAMBARAN STATUS EKONOMI DAN TINGKAT PENDIDIKAN ORANG TUA TERHADAP STATUS GIZI BALITA - Wijayanti, Anita; Theresia, Endah Marianingsih; Rahmawati, Anita (Jurnal Kesehatan Ibu dan Anak, 2015)
Yogyakarta city has a highest malnutrition coverage than another district regency in Daerah Istimewa Yogyakarta. Prevalence of infant malnutrition in four districts in Yogyakarta province have appropriate expectations, that is <1%, meanwhile in Yogyakarta city still 1.35%. Themost malnutritions problemhas discovered in sub-districtGondokusuman accupation zoneGondokusuman's public health center. Malnutrition appear result by many environmental factors, which are caused by economic status and education level.The education level parents also determined a nutritional status of children because education most affects a person to know and receive information about nutrition. That's known there are 30.8% poor household concerning inhabitant quantity in Gondokusuman's district. In public health center Gondokusuman 1, Demangan village has the highest percentage of poor families. The highest incidence of malnutrition also exist in the Demangan village. This research aims to describe the economic status and education level parents on nutritional status of children. Amethod used in this research are descriptivemethod with cross sectionaldesign. Data analysis are using descriptive analysis techniques with statistical tests used proportions. Results showed that the economic status of parents who have toddlers entirely enough good nutritional status. Meanwhile a parents with lack economic status is having a toddler with a diverse nutritional status are many kind nutritional status, decrease, and more. Parents who have a great education will have a good nutritional status of children. Parents are the primary and secondary education has nourished toddlers also varies.